2006
DOI: 10.1093/nar/gkl673
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprecipitation of spliceosomal RNAs by antisera to galectin-1 and galectin-3

Abstract: We have shown that galectin-1 and galectin-3 are functionally redundant splicing factors. Now we provide evidence that both galectins are directly associated with spliceosomes by analyzing RNAs and proteins of complexes immunoprecipitated by galectin-specific antisera. Both galectin antisera co-precipitated splicing substrate, splicing intermediates and products in active spliceosomes. Protein factors co-precipitated by the galectin antisera included the Sm core polypeptides of snRNPs, hnRNP C1/C2 and Slu7. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 22 publications
2
48
1
Order By: Relevance
“…Our data provide strong evidence that the reduction of contact allergy responses induced by galectin-2 injections was primarily mediated by impaired CD8 ϩ T cell effector function. T cell-mediated autoimmune or delayed-type hypersensitivity responses can be suppressed by regulatory CD4 ϩ CD25 ϩ T cells (47). Indeed, galectin-1 treatment reduced the development of experimental autoimmune uveitis in mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…Our data provide strong evidence that the reduction of contact allergy responses induced by galectin-2 injections was primarily mediated by impaired CD8 ϩ T cell effector function. T cell-mediated autoimmune or delayed-type hypersensitivity responses can be suppressed by regulatory CD4 ϩ CD25 ϩ T cells (47). Indeed, galectin-1 treatment reduced the development of experimental autoimmune uveitis in mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility, currently under investigation, is that GAL3 may interact with the RNA-binding proteins heterogeneous nuclear ribonucleoproteins to control PTEN RNA turnover. It has been previously reported that GAL3 binds directly to hnRnpA1 (54) and heterogeneous nuclear ribonucleoprotein C1/C2 (55) and that heterogeneous nuclear ribonucleoproteins form a multiprotein complex that regulates c-fos RNA degradation (56) and inhibit the mRNA editing action of Apobec (57). Binding of P-GAL3 to PTEN may also potentially alter the spatial structure of PTEN affecting its degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Two remarkable Gal-1 intracellular functions discovered so far are the membrane anchorage of the oncogene H-Ras [20] and the interaction with spliceosomes via Gemin4 [21]. Neither of these functions requires sugar binding activity of Gal-1 [22,23].…”
Section: Introductionmentioning
confidence: 99%